The challenges of obstetric nursing in the beginning of the COVID-19 pandemic in the state of Pará (Research, Society and Development, 2021)
This study aimed to report the experience on the obstetric nursing challenges in the context of the beginning of the COVID-19 pandemic in Pará, a state of Brazil. This is a descriptive study as an experience report carried out during the pandemic of the new Coronavirus, on the obstetric care provided, from March to August 2020. In the results, it is highlighted that from the epidemiological bulletins, it was demonstrated that among the states that most concentrated deaths of pregnant women due to COVID-19, Pará occupies the 6th place with 08 registered cases, until 08/01/2020. In the obstetric field during the pandemic, in the initial and critical months of the disease in Brazil, several difficulties and obstacles were observed in the flow and structure of obstetric care in the fields of nursing practice There were countless removals of professionals, as they are at risk, and even, the interruption of prenatal care with cancellation of consultations during the complicated phase of high rates of the disease. Thus, one must reflect the challenges that the nurse professional faced and must overcome when experiencing the COVID-19 pandemic with regard to their obstetric care.